Analysis of financial performance budget absorption in production forest areas in Karawang regency - Didit Supriyadi; Yosep Yudianto; Mayadita Kapriyanti; Kukuh Wahyu Nugroho (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The aim of this research is to investigate and identify the relationship and influence between several key factors on budget absorption and financial performance in the production forest area of Karawang Regency. This research explores it comprehensivelyand analyze the causal relationship between budget planning, budget implementation, and the government's internal control system on budget absorption, as well as the impact of budget absorption on financial performance. The research method used was a quantitative description technique involving 200 respondents as samples. Path analysis is used as a quantitative data analysis tool in this research. The research results revealed several significant findings regarding the influence of certain factors on aspects of budget absorption and financial performance in production forest areas in Karawang Regency. First, budget planning is proven to have a significant impact on budget absorption in the forestry production area. Second, budget compliance is also closely related to budget absorption, especially in the Karawang production forest area. Third, the government's internal management system also influences budget absorption in the region. Furthermore, the fourth finding shows that budget absorption has contributed to financial performance in the Karawang production forest area. In addition, research highlights the mediating role of budget absorption, where budget absorption functions as a link between budget planning and financial performance, between household implementation and financial performance, as well as between the government's internal management system and financial performance. Thus, these findings provide in-depth insight into the complex relationship between these factors and highlight the central role of budget absorption in achieving optimal financial performance in the Karawang Regency production forest area.